The Economic Afterlife of the Dead: Macroeconomic Impacts of the Metaverse, Digital Inheritance, and Artificial Intelligence Inflation - Berat Akıncı; Filiz Kutluay Tutar; Abdallah Abukalloub (CV. Media Digital Publikasi Indonesia, 2026)
This article examines the macroeconomic implications of the emerging postmortem economy at the intersection of artificial intelligence (AI), the metaverse, digital inheritance, and autonomous digital agency. Conventional macroeconomic models typically define production in terms of physical capital and biologically living human labor. However, the rise of autonomous digital twins, orphaned algorithms, posthumous AI agents, and inherited digital assets challenges this traditional distinction. Digital assets and AI-mediated representations may continue to generate economic value after the death of their original human owners, raising new questions for production theory, inflation dynamics, taxation, liquidity, and income distribution. To address this gap, this article proposes the “ghost factor of production” and introduces “ghost capital” as an analytical category for modeling autonomous and posthumous digital productive capacity. Rather than claiming that deceased individuals continue to work, the framework conceptualizes how data, digital assets, synthetic identities, AI agents, and digital twins may extend economic agency beyond biological life. This article further examines the asymmetric price dynamics associated with AI adoption, defined here as “AI inflation,” and explores how ghost-to-ghost (G2G) commerce among autonomous digital agents may affect liquidity, taxation, and intergenerational wealth distribution. Using conceptual system dynamics and a scenario-based simulation framework, the study discusses potential digital asset liquidity traps and inheritance-tax paradoxes. The article contributes to debates on digital inheritance, AI-mediated production, and metaverse economies by offering a new macroeconomic perspective on postmortem digital agency.